NILAI-NILAI PENDIDIKAN ISLAM DALAM FABEL “SI KANCIL MENCURI TIMUN” - Saepudin Saepudin; Miftahudin Miftahudin; Hanafi Hanafi (Jurnal Anak Bangsa, 2023)
This research aimed to describe the values of Islamic education contained in fable “The Deer Stole the Cucumber”. This research is a library research with a qualitative approach. The focus of this research is a moral message that must be applied in a real-life accordance to Islamic teachings. The instrument of the research is the researcher himself, using content analysis techniques. The research result concluded that reading fables “The Mouse Deer Stole the Cucumber” to children is moral education also contains the values of Islamic religious educations such as: humans should make an effort as much as possible and prohibited to commit act of stealing other people’s property because it will harm others, and always be patient in all circumstances